Sprayable Thin and Robust Carbon Nanofiber Composite Coating for Extreme Jumping Dropwise Condensation Performance. Issue 1 (25th November 2020) - Donati, Matteo; Lam, Cheuk Wing Edmond; Milionis, Athanasios; Sharma, Chander Shekhar; Tripathy, Abinash; Zendeli, Armend; Poulikakos, Dimos
Abstract: Condensation of water on metallic surfaces is critical for multiple energy conversion processes. Enhancement in condensation heat transfer efficiency often requires surface texturing and hydrophobicity, usually achieved through coatings, to maintain dropwise condensation. However, such surface treatments face conflicting challenges of minimal coating thermal resistance, enhanced coating durability, and scalable fabrication. This study presents a thin (≈2 µm) polytetrafluoroethylene–carbon nanofiber nanocomposite coating that meets these challenges and sustains coalescence‐induced jumping droplet condensation for extended periods under highly demanding condensation conditions. Coating durability is achieved through improved substrate adhesion by depositing a submicron thick aluminum primer layer. Carbon nanofibers in a polytetrafluoroethylene matrix increase coating thermal conductivity and promote spontaneous surface nanotexturing to achieve superhydrophobicity for condensate microdroplets. The coating material can be deposited through direct spraying, ensuring economical scalability and versatility for a wide range of substrates. No other coating is known for metallic surfaces that is able to sustain jumping dropwise condensation under shear of steam at 111 °C flowing at ≈3 m s −1 over the surface for 10 h and dropwise condensation for an additional 50 h. Up to ≈900% improvement in condensation heat transfer coefficient is achieved compared to conventional filmwise condensation. Abstract : An extremely durable and sprayable superhydrophobic carbon nanocomposite coating for condensation is presented. Superhydrophobicity from the hierarchical structure of the coating enables jumping dropwise condensation, leading to a ninefold heat transfer improvement. The nanocomposite, reinforced by carbon nanofibers, can sustain continuous jumping dropwise condensation for about 10 h under high temperature and high shear steam conditions.